Spectrum Of Histomorpholological Patterns Of Meningioma At A Tertiary Health Centre (Journal of Pharmaceutical Negative Results, 2022)
Aim: To study various histomorphological patterns observed in meningiomas.Material and methods: The present cohort study was conducted for a period of 4 years on40 meningioma specimens received in histopathology department from AVBRH hospital and Department of Pathology, Jawaharlal Nehru Medical College, DMIMS (DU), Sawangi, Wardha, Maharashtra. Cases were analyzed in detail about the complete clinical history, exact location, clinical and radiological diagnosis. All the specimens were thoroughly grossed, sectioned, and stained with H & E. Cases were reported taking into consideration all the clinicoradiological features in relation to age, sex, duration, site, symptoms in addition to the histomorphological features and WHO grading system.Results: Females (65%) were comparatively more as compared to males (35%). Maximum subjects were from the age group of 41-50 years (42.5%) followed by 51-560 years (25%). Histology revealed meningothelial meningioma as the most common variant followed by psammomatous meningioma. WHO grade I, II and III was reported 36, 2 and 2 cases respectively. WHO grade II was revealed in atypical meningioma while grade III in anaplastic and papillary meningioma.Conclusion: Meningioma is a slow growing benign neoplasm which presents with a wide range of clinical features and has a female predominance. Many histological variants occur with the meningothelial type being reported as the commonest. WHO Grade I tumors and those with complete surgical resection have good prognosis. Hence correct histological grading and typing are essential as few histological subtypes have higher risk of recurrence.